2014
DOI: 10.1038/oncsis.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor NDRG2 tips the balance of oncogenic TGF-β via EMT inhibition in colorectal cancer

Abstract: Transforming growth factor-beta (TGF-β), a pluripotent cytokine expressed in the colon, has a crucial but paradoxical role in colorectal cancer (CRC). TGF-β is a potent proliferation inhibitor of normal colon epithelial cells and acts as a tumor suppressor. However, TGF-β also promotes invasion and metastasis during late-stage CRC, thereby acting as an oncogene. Thus, understanding the factors behind the paradoxical roles of TGF-β and elucidating the mechanisms by which TGF-β-induced proliferation inhibition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 47 publications
2
62
0
Order By: Relevance
“…Cancer cells undergoing EMT acquired invasive properties. Numerous studies have illustrated that EMT is a common molecular mechanism in colorectal cancer metastasis, and many proteins contribute to this process (21,22). Taking this into consideration, we hypothesized that LASP1 is involved in EMT-mediated colorectal cancer metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Cancer cells undergoing EMT acquired invasive properties. Numerous studies have illustrated that EMT is a common molecular mechanism in colorectal cancer metastasis, and many proteins contribute to this process (21,22). Taking this into consideration, we hypothesized that LASP1 is involved in EMT-mediated colorectal cancer metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, NDRG2 was confirmed as a target of miR-486 and NDRG2 expression could be negatively regulated by miR-486. NDRG2 is proposed to be a tumor suppressor gene that plays a key role in the development of diverse human cancers [23][24][25][26]. Interestingly, a previous study had discovered that NDRG2 in the heart is modulated by myocardial I/R and may be involved in I/R-induced cardiac tissue injury [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the case of vimentin, in which Sp1 and Smad together act as a switch for vimentin expression, these two transcription factors may function to regulate the St6gal1 expression independently, because deletion of the putative Smad binding sites within the St6gal1 promoter only decreased the efficiency of St6gal1 induction instead of completely abrogating its promoter activity. Recently, Sp1 and Smad proteins have been found to control the expression of tumor suppressor NDRG2 in a similar way during the TGF-␤-induced EMT (48). These observations raise the question of how this regulatory strategy of St6gal1/NDRG2 expression benefits the cells.…”
Section: Discussionmentioning
confidence: 99%